Beauty and good in Aristotle (Iter, 2022)
A key issue in Aristotle s Poetics is the independence or autonomy of Litera ture, particularlynith respect to moral. In this respect. Aristotle ñas the flrst to tackle the literary theme scientifically.establishing distinctions and setting up precisions that are valid even non . more than tn enh'centuries after. Although Literature is the solé frame of considerations in his Poetics. n e can say'that this n ork marks the foundation of Aesthetics as an autonomous discipline.
Keywords: Aristotle: Poetics: Plato: Ethics: Aesthetics: art